Analysis of the influencing factors of left-behind children's mental health based on python program--Anhui Province as an example - Ding, Wenhui; Sun, Yanling (International Journal of Global Economics and Management, 2024)
With the rapid development of social economy, the number of farmers going to the cities to work has increased, leading to the problem of left-behind children in rural areas. Left-behind children face physical and mental health challenges due to the lack of parental accompaniment. The state has introduced policies to improve their environment, but uneven educational resources, psychological problems and lagging rural development remain to be solved. Based on the data of left-behind children in Anhui Province during the seven-year period of 2016-2022, this paper collates relevant literature and then empirically analyses the factors affecting the number of left-behind children and their mental health by means of multiple linear regression models. The study shows that the number of left-behind children has a strong negative correlation with economic growth and education problems, which means that improving the economic and educational conditions may help reduce the number of left-behind children, while the family environment and campus environment have a significant positive effect on the mental health of left-behind children. Finally, on the basis of the empirical findings, policy initiatives such as promoting economic growth and employment opportunities, improving the distribution of educational resources, strengthening family care and companionship, optimising the campus environment and teacher-student relationship, and establishing a peer support mechanism and are proposed in the hope of creating a better environment for left-behind children to grow up, and then promoting their psychological health development.